Q-switching pulses generation with samarium oxide film saturable absorber - Nur F., Zulkifli; Malathy*, Batumalay; Farina, S.M.Samsamnun; Mohamad, B.H.Mahyuddin; Tengku F., T.M.N.Izam; Muhammad I.M., A.Khudus; Sulaiman, W.Harun (Wiley Online Library, 2019)
Q‐switching pulses generation in an erbium‐doped fiber laser (EDFL) was demonstrated by using a samarium oxide (Sm2O3) film as a saturable absorber (SA) for the first time. The passively Q‐switched EDFL operated stably at 1567 nm with tunable repetition rates, ranging from 47 to 66 kHz with the increase in pump power from 51.0 to 88.1 mW. At 88.1 mW pump power, the maximum pulse energy and the minimum pulse width were obtained at 26 nJ and 5.6 μs, respectively. These results demonstrated that the proposed Sm2O3 SA is viable for the construction of a flexible and reliably stable Q‐switched pulsed fiber laser in the 1.5 μm region.